Determining the Optimum Replacement Time of Dosing Pump Components Using the Age Replacement Model (Case Study at PDAM Tirtawening Bandung) - Julita Nahar (International Journal of Quantitative Research and Modeling, 2025)
The increase in population over time has a direct impact on the rising demand for clean water supply services, making the availability and management of water resources an increasingly critical aspect. To maintain water quality and supply continuity, reliable production machines are required. One of the machines used is a dosing pump, whose critical component is the valve ring. To ensure continuous operation without machine failure during the production process, appropriate maintenance is required by determining the optimum replacement time interval for the valve ring component using the Age Replacement model. The results of the data analysis show that the failure of the valve ring component follows a Nonhomogeneous Poisson Process (NHPP) with a Power Law Process (PLP) failure model. The optimum replacement time for the valve ring component based on the Age Replacement model is every 103.87 days of operation with a total replacement cost risk of Rp. 925,063.20, and this model is able to reduce the replacement cost of the valve ring component by 46.72%.